Engineering Problems Uncertainties, Constraints and Optimization Techniques - Tsuzuki, Marcos S.G; Takimoto, Rogério Y.; Sato, André K.; Saka, Tomoki; Barari, Ahmad; Abdel Rahman, Rehab O.; Hung, Yung-Tse (IntechOpen, 2022)
This book is based on the concept that optimization, as the core engineering practice, is a bridge to relate the given problem constraints to an acceptable level of uncertainties for the corresponding solution. Over two sections, this book addresses optimization techniques and parameters for engineering problems, corresponding uncertainties in engineering optimization solutions and methods to manage them, and managing uncertainties to support environmental pollution prevention and control.